2002
DOI: 10.1080/08990220220131505
|View full text |Cite
|
Sign up to set email alerts
|

A four-channel analysis of the tactile sensitivity of the fingertip: frequency selectivity, spatial summation, and temporal summation

Abstract: Thresholds were measured for the detection of vibratory stimuli of variable frequency and duration applied to the index fingertip and thenar eminence through contactors of different sizes. The effects of stimulus frequency could be accounted for by the frequency characteristics of the Pacinian (P), non-Pacinian (NP) I, and NP III channels previously determined for the thenar eminence (Bolanowski et al., J Acoust Soc Am 84: 1680-1694, 1988; Gescheider et al., Somatosens Mot Res 18: 191-201, 2001). The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
134
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 43 publications
26
134
4
Order By: Relevance
“…The performance of the four human subjects in the present study agreed with the available data for the human hand, with best sensitivity of 250 Hz. The notch at 20 Hz in the human sensitivity curves is consistent with the data from previous studies and is representative of a shift in the receptors that mediate the sensation of vibration (Johansson et al, 1982;Gescheider et al, 2002;Morioka and Griffin, 2005). The similarities in the performance of the human subjects in the present study to prior measures of tactile sensitivity for humans confirms the accuracy of the experimental methods used and provides further confidence in the measured thresholds for the seal.…”
Section: Validity Of Vibrotactile Threshold Measurementssupporting
confidence: 88%
“…The performance of the four human subjects in the present study agreed with the available data for the human hand, with best sensitivity of 250 Hz. The notch at 20 Hz in the human sensitivity curves is consistent with the data from previous studies and is representative of a shift in the receptors that mediate the sensation of vibration (Johansson et al, 1982;Gescheider et al, 2002;Morioka and Griffin, 2005). The similarities in the performance of the human subjects in the present study to prior measures of tactile sensitivity for humans confirms the accuracy of the experimental methods used and provides further confidence in the measured thresholds for the seal.…”
Section: Validity Of Vibrotactile Threshold Measurementssupporting
confidence: 88%
“…It would be interesting to find what the limit value of the difference in finger skin temperature at 63 Hz that would induce a significant effect on VPT should be. As revealed by the studies conducted by Bolanowski et al [23] and Gescheider et al [24] there is no evident boundary between vibration perception by the Meissner corpuscles or the Pacinian corpuscles. Accordingly, it is only at the frequency of 125 Hz that induces the highest perception sensitivity of …”
Section: Discussionmentioning
confidence: 62%
“…Studies of vibrotactile perception by Bolanowski, Gescheider, Verrillo and co-workers [13,14,15] led to an understanding of the properties of the four information-processing channels in the glabrous skin by applying a small vibrating probe (varying from 0.1 to 2.9 cm 2 ) with a surround (usually 1 mm gap between the probe and the surround) to the fingertip or the thenar eminence to elicit, or isolate, responses from a particular tactile channel. Morioka and Griffin [4] extended this to the palmar area of the hand by examining the effect of contact area and contact location on thresholds of perception of vibration applied to the fingertip and the hand and concluded that thresholds for the perception of vibration applied to the whole area of the hand seemed to be mediated by the Pacinian, NP I and NP II channels with some influence of biodynamic responses.…”
mentioning
confidence: 99%